Peranan Dinas Pendidikan dan Kebudayaan Kabupaten Serang Dalam Pelaksanaan Diklat Calon Kepala Sekolah Dengan Metode Hybrid Learning - Awan Dharmawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This study aims to determine the role of the Education and Culture Office of Serang Regency in the implementation of the Training for Candidates for Principals of Elementary Schools (SD) and Junior High Schools (SMP) using the Hybrid Learning method or a combination of in-network (online) and off-network (Offline) in year 2020-2021.This research uses descriptive qualitative method. In answering the research problem, a role theory approach is used (Anis Rachma Utary, 2014) which is related to the title. Observations were made by conducting interviews with 6 key informants and additional informants. From the results of observations made then analyzed and interpreted to obtain the expected research results. The results of the analysis and interpretation show that the role carried out by the Education and Culture Office of Serang Regency in the implementation of Training for Candidate Principals for Elementary Schools - Middle Schools in a combination between online (Online) and off-Network (Offline) or Hybrid Learning in 2020-2021 is appropriate and optimal. . These results indicate that for the future the Education and Culture Office of Serang Regency must make new breakthroughs in carrying out similar activities to further increase its role, especially if the Covid 19 pandemic continues for the next few years.